Psychomotor Retardation and the prognosis of antidepressant treatment in patients with unipolar Psychotic Depression. (November 2020) - Janzing, Joost G.E.; Birkenhäger, Tom K.; van den Broek, Walter W.; Breteler, Leonie M.T.; Nolen, Willem A.; Verkes, Robbert-Jan
Abstract: Background: Psychomotor Retardation is a key symptom of Major Depressive Disorder. According to the literature its presence may affect the prognosis of treatment. Aim of the present study is to investigate the prognostic role of Psychomotor Retardation in patients with unipolar Psychotic Depression who are under antidepressant treatment. Methods: The Salpetriere Retardation Rating Scale was administered at baseline and after 6 weeks to 122 patients with unipolar Psychotic Depression who were randomly allocated to treatment with imipramine, venlafaxine or venlafaxine plus quetiapine. We studied the effects of Psychomotor Retardation on both depression and psychosis related outcome measures. Results: 73% of the patients had Psychomotor Retardation at baseline against 35% after six weeks of treatment. The presence of Psychomotor Retardation predicted lower depression remission rates in addition to a higher persistence of delusions. After six weeks of treatment, venlafaxine was associated with higher levels of Psychomotor Retardation compared to imipramine and venlafaxine plus quetiapine. Conclusions: Our data confirm that Psychomotor Retardation is a severity marker of unipolar Psychotic Depression. It is highly prevalent and predicts lower effectivity of antidepressant psychopharmacological treatment.